CRISPR/Cas9-Mediated Targeted Mutagenesis of FtMYB45 Promotes Flavonoid Biosynthesis in Tartary Buckwheat (Fagopyrum tataricum) - Wen, Dong; Wu, Lan; Wang, Mengyue; Yang, Wei; Wang, Xingwen; Ma, Wei; Sun, Wei; Chen, Shilin; Xiang, Li; Shi, Yuhua (Frontiers in Plant Science, 2022)
The clustered regularly interspaced short palindromic repeat/CRISPR-associated protein 9 (CRISPR/Cas9) technology is an efficient genome editing tool used in multiple plant species. However, it has not been applied to Tartary buckwheat (Fagopyrum tataricum), which is an important edible and medicinal crop rich in rutin and other flavonoids. FtMYB45 is an R2R3-type MYB transcription factor that negatively regulates flavonoid biosynthesis in Tartary buckwheat. Here, the CRISPR/Cas9 system polycistronic tRNA-sgRNA (PTG)/Cas9 was employed to knock out the FtMYB45 gene in Tartary buckwheat. Two single-guide RNAs (sgRNAs) were designed to target the second exon of the FtMYB45 gene. Twelve transgenic hairy roots were obtained using Agrobacterium rhizogenes-mediated transformation. Sequencing data revealed that six lines containing six types of mutations at the predicted double-stranded break site were generated using sgRNA1. The mutation frequency reached 50%. A liquid chromatography coupled with triple quadrupole mass spectrometry (LC-QqQ-MS) based metabolomic analysis revealed that the content of rutin, catechin, and other flavonoids was increased in hairy root mutants compared with that of lines transformed with the empty vector. Thus, CRISPR/Cas9-mediated targeted mutagenesis of FtMYB45 effectively increased the flavonoids content of Tartary buckwheat. This finding demonstrated that the CRISPR/Cas9 system is an efficient tool for precise genome editing in Tartary buckwheat and lays the foundation for gene function research and quality improvement in Tartary buckwheat.